The effect of 8-week hemsball training on balance, reactive agility and lower extremity strength - Ozan Sever; Suleyman Gonulates; Akan Bayraktar; Erdal A Zorb; Zinnur Gerek; Gokhan Ipekoglu (Türk Spor ve Egzersiz Dergisi)
This study was designed to investigate the effects of hemsball training, upon reactive agility, balance and vertical jump tests. 80 participants, 50 of whom were the experimental group (8,82± 1,44 years) and 30 of whom (9,00 ± 1,19 years) were the control group, took part in the study. While the experimental group had 1-hour training on three days of week throughout 8 weeks, no training was done to the control group. The pre and post test results revealing both the in-group variance and differences between the groups was analyzed with the multivariate analysis of variance in repeated measurements (MANOVA) by using SPSS 19 analysis software. It was seen that the participants who played hemsball had %36,85 progress, increasing their stork balance scores from 4,45 seconds to 6,09 seconds. While this progress made a statistically significant difference (p lt;0.05), the same progress did not improve for the control group (p gt;0,05). There is not any significant in-group or intergroup difference in other tests. It was revealed that hemsball training improves balance skills in children. It is beneficial to integrate hemsball trainings into the training programs which focus on balance improvement-maintenance.